2015
DOI: 10.1139/cjes-2015-0142
|View full text |Cite
|
Sign up to set email alerts
|

Two garnet growth events in polymetamorphic rocks in southwest Spitsbergen, Norway: insight in the history of Neoproterozoic and early Paleozoic metamorphism in the High Arctic

Abstract: Geochronological studies in northern Wedel Jarlsberg Land, southwestern Svalbard (Norway), showed that the Tonian (c. 950 Ma) igneous rocks were subjected to metamorphism during the Torellian (c. 640 Ma) and early Caledonian (470–460 Ma) events. Predominant augen gneisses, derived from a Tonian protolith, are intercalated in that area, with schists comprising two distinct metamorphic mineral assemblages. The M1 (Torellian) assemblage containing garnet-I + quartz + plagioclase-I + biotite-I + muscovite-I was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Retrograde blueschists from Nordenskiöld Land yielded P-T conditions of 14-18 kbar by 470-490 °C and confirmed a low 7-8 °C/km subduction gradient [25]. Majka et al [33] have reported on 9-12 kbar and c. 500-550 °C P-T conditions for the Caledonian metamorphic overprint of the Berzeliuseggene unit.…”
Section: Caledonian Orogenymentioning
confidence: 86%
See 4 more Smart Citations
“…Retrograde blueschists from Nordenskiöld Land yielded P-T conditions of 14-18 kbar by 470-490 °C and confirmed a low 7-8 °C/km subduction gradient [25]. Majka et al [33] have reported on 9-12 kbar and c. 500-550 °C P-T conditions for the Caledonian metamorphic overprint of the Berzeliuseggene unit.…”
Section: Caledonian Orogenymentioning
confidence: 86%
“…The retrograde blueschists can be traced south of Oscar II Land in Nordenskiöld Land near Marvågen and Orustosen as shown by Kośmińska et al [25]. Also, the polymetamorphic rocks of the Berzeliuseggene unit are overprinted by the HP metamorphic event of inferred Caledonian age ( [9,33] and references therein). The only reliable ages derived for the greenschist facies rocks come from the southern part of Wedel Jarlsberg Land and have been published by Manecki et al [34].…”
Section: Caledonian Orogenymentioning
confidence: 99%
See 3 more Smart Citations